Essentials of psychological testing - Urbina, Susana, 1946- (Essentials of behavioral science series., 2014)
"An engaging, practical guide to psychological testingEssentials of Psychological Testing, 2nd Edition is a fully updated and revised overview of the basic principles of psychometrics, including the information needed to understand and evaluate tests. It contains everything you need to know about the science of measuring knowledge, abilities, attitudes, personality traits, and education level, and introduces readers to the most relevant reference works in the field. This guide was written specifically for active professionals and students in fields ranging from clinical mental health and social work to education and human resources. In Essentials of Psychological Testing, 2nd Edition, even the most complicated psychometric principles are made interesting and easy to comprehend. More importantly, you will learn how to translate this new knowledge into practice by selecting the right tests, administering them appropriately, and correctly interpreting results. Dr. Susana Urbina describes the science of psychometrics, along with its history, providing important background information for the sections that follow. You'll find detailed information on testing procedures, score interpretation, reliability and validity, and "Test Yourself" questions that help activate your knowledge. In addition, the Second Edition has been updated to include: Information from the revised Standards for Educational and Psychological Testing New examples from the most recent versions of psychological tests Discussion of new test administration technologies, such as the Q-Interactive Illustrations and easy-to-find reinforcement of key concepts Dr. Urbina is recognized as a leading expert in the field of psychometrics, and her enjoyable writing style makes it easy to master this complex subject. Essentials of Psychological Testing, 2nd Edition is required reading for anyone who needs to know what psychological tests are and how to use them in a professional, consistent, scientifically sound manner"--